Enhancing the storage life and marketability of orange cape gooseberry fruit: Melatonin treatment boosts the enzymatic antioxidant system - Taghipour Leila; Hayati Parisa; Hosseinifarahi Mehdi; Assar Pedram (Journal of Agricultural Sciences (Belgrade))
The cape gooseberry fruit (Physalis peruviana L.) is a climacteric fruit that experiences significant color and texture changes during storage due to increased ethylene synthesis. While its storage life with its calyx is one month, it only lasts 4 to 5 days without it. Therefore, strategies to reduce postharvest losses and extend storage life are essential. In this study, entirely ripe orange cape gooseberry fruits with yellow calyces were harvested and transferred to the laboratory. After washing, the fruits were immersed in melatonin solutions at concentrations of 100, 200, and 300 µM for 5 minutes, with distilled water as a control. The fruits were stored at 10°C and 90 ± 5% relative humidity for 21 days and evaluated weekly. The results showed that all melatonin treatments significantly controlled weight loss and fruit softening. Melatonin-treated fruits also had a comparable taste index and performed better than the controls. Melatonin treatment improved the antioxidant enzymatic system, with fruits treated with 300 µM melatonin showing the highest activities of superoxide dismutase, catalase, ascorbate peroxidase, and peroxidase enzymes, and the lowest hydrogen peroxide content, indicating reduced oxidative stress. Additionally, the lowest decay (17.4%) was observed in fruits treated with 300 µM melatonin, while the highest decay (43.83%) occurred in control fruits. Melatonin treatment proved to be effective in improving the quality and extending the shelf life of cape gooseberry fruits, acting as a valuable and environmentally friendly postharvest preservation method by delaying ripening, enhancing enzymatic antioxidant activity, and preserving taste index.